Thermal-Induced Oxygen Vacancy Enhancing the Thermo-Chromic Performance of W-VO2−x@AA/PVP Nanoparticle Composite-Based Smart Windows - Jiran Liang; Tong Wu; Chengye Zhang; Yunfei Bai; Dequan Zhang; Dangyuan Lei (Nanomaterials, 2025)
Tungsten-doped vanadium dioxide (W-VO2) shows semiconductor-to-metal phase transition properties at room temperature, which is an ideal thermo-chromic smart window material. However, low visual transmittance and solar modulation limit its application in building energy saving. In this paper, a W-VO2−x@AA core-shell nanoparticle is proposed to improve the thermo-chromic performance of W-VO2. Oxygen vacancies were used to promote the connection of W-VO2−x nanoparticles with L-ascorbic acid (AA) molecules. Oxygen vacancies were tuned in W-VO2 nanoparticles by thermal annealing temperatures in vacuum, and W-VO2−x@AA nanoparticles were synthesized by the hydrothermal method. A smart window was formed by dispersing W-VO2−x@AA core-shell nanoparticles into PVP evenly and spin-coating them on the surface of glass. The visual transmittance of this smart window reaches up to 67%, and the solar modulation reaches up to 12.1%. This enhanced thermo-chromic performance is related to the electron density enhanced by the AA surface molecular coordination effect through W dopant and oxygen vacancies. This work provides a new strategy to enhance the thermo-chromic performance of W-VO2 and its application in the building energy-saving field.